THE CORRELATION OF MARKERS OF ENDOGENIC INTOXICATION AND IMMUNITY IN PATIENTS WITH CHRONIC PYELONEPHRITIS AND EFFICACY OF DIFFERENT SCHEMES OF TREATMENT - T. Mylnikova; l. Martynuk; G. Symko; I. Yakubyshyna (Ukrainian Journal of Nephrology and Dialysis, 2017)
The purpose of study was to analize the correlation between the rate of syndrom of endogenic intoxication (EI) and the markers of immunity in patients with chronic pyelonephritis (PN). To research the effectiveness of different schemes of treatment chronic pyelonephritis.Methods. Researched were the syndrom of EI and the some markers of immunity in 135 patients with chronic PN. The correlation analysis was performed. For estimate of effectiveness of different schemes of treatment the patients were divided into 4 groups.Results. A growing of deficit of T-cells immunity markers such as CD3+, CD4+ та CD8+ was found and the rising of rate Ig А, G and the circulated immune complexes with increasing of EI. The research showed the rising of spontaneous production TNF- ά and decrease of rate IL-10 with deepening of intoxication.Conclusions. Decreasing of cell-mediated and increasing of humoral immunity markers in patients with exacerbation of chronic PN were found. It was found that there was faster regress of clinical symptomatic in patients that got prescriptions treatment including Kanephron and Chophytol.